2003
DOI: 10.1097/01.ta.0000062968.69867.6f
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Resuscitation Strategies: A Systematic Review of Animal Trials

Abstract: Fluid resuscitation appears to reduce the risk of death in animal models of severe hemorrhage but increases the risk of death in those with less severe hemorrhage. Excessive fluid resuscitation could therefore be harmful in some situations. Hypotensive resuscitation reduced the risk of death in all the trials investigating it. An evaluation of the potential impact of hypotensive resuscitation in humans could now be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
1
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(127 citation statements)
references
References 37 publications
3
115
1
8
Order By: Relevance
“…The mortality rate (7.3%) was the same for both groups of patients. However, comparison of Injury Severity Scores 26 indicated that patients in the low group (scores, [16][17][18][19][20][21][22][23][24] were more severely injured (P = .02) than were patients in the conventional group (scores, 9-15). Thus, permissive hypotensive resuscitation may benefit restoration of blood circulation and cause a modest increase in blood pressure (reducing the risk of additional blood loss due to continued bleeding or rebleeding) with minimal fluid requirements.…”
Section: Studies Of Permissive Hypotension In Humansmentioning
confidence: 95%
See 1 more Smart Citation
“…The mortality rate (7.3%) was the same for both groups of patients. However, comparison of Injury Severity Scores 26 indicated that patients in the low group (scores, [16][17][18][19][20][21][22][23][24] were more severely injured (P = .02) than were patients in the conventional group (scores, 9-15). Thus, permissive hypotensive resuscitation may benefit restoration of blood circulation and cause a modest increase in blood pressure (reducing the risk of additional blood loss due to continued bleeding or rebleeding) with minimal fluid requirements.…”
Section: Studies Of Permissive Hypotension In Humansmentioning
confidence: 95%
“…18 Aggressive fluid resuscitation may reverse vasoconstriction by replacing volume, displace early formed thrombus by increasing blood flow, and therefore magnify the establishment of coagulopathy due to hypovolemic shock. 20 A systematic meta-analysis of preclinical data (52 animal trials) 21 indicated an increased adjusted relative risk of death, from 0.69 to 1.80, when aggressive resuscitation was used in animals with less severe hemorrhage (ie, tail resection). In other trials, 16,17 attempts to increase MAP to 80 mm Hg with fluid resuscitation in animals with established hypovolemic shock were associated with decreased oxygen supply to the tissues, metabolic acidosis, and a poor outcome.…”
Section: Experimental Assessment Of Permissive Hypotension In Animalsmentioning
confidence: 99%
“…This hypotensive approach has been adopted in civilian [6] and military [7] authority publications, advocating limited initial fluid resuscitation to resuscitate the trauma casualty in order to maintain a target systolic blood pressure of 80 mmHg (approximating to a palpable radial pulse). A systematic review of animal studies concluded that all the studies of hypotensive resuscitation strategies reduced the risk of death when compared with normotensive strategies [8]. However, the vascular injury used (e.g.…”
Section: Volume Resuscitation In Major Traumamentioning
confidence: 99%
“…Patients with penetrating truncal trauma, in which resuscitation was delayed, had a higher survival rate to discharge (70%) compared with promptly resuscitated patients (62%, P = 0.04) [4]. Likewise, a systemic review of animal studies [5] has also shown a lower risk of death in animals resuscitated to hypotensive levels than in animals resuscitated to normotensive levels (P \ 0.00001). The small volume resuscitation with fluids such as hypertonic saline [6] or albumin 25% [7] has similarly shown a higher survival rate compared with infusion of isotonic fluids.…”
mentioning
confidence: 98%
“…Recently, the importance of limited resuscitation [4][5][6][7] has been widely acknowledged. Patients with penetrating truncal trauma, in which resuscitation was delayed, had a higher survival rate to discharge (70%) compared with promptly resuscitated patients (62%, P = 0.04) [4].…”
mentioning
confidence: 99%